“Should I stay or Should I go”: patient who leave Emergency Department of an Italian Third-Level Teaching Hospital - Carli, Alberto; Moretti, Francesca; Giovanazzi, Giulia; Niero, Valentina; Perilli, Valeria; Ghirlanda, Giovanna; Bovo, Chiara; Tardivo, Stefano (Acta Biomedica Atenei Parmensis, 2018)
Background and Aim: Patients could leave ED not receiving the desired care either Without Being Seen by a doctor (LWBS) or Against Medical Advice (DAMA). In term of care quality, LWBS may be related to inappropriate access and process of care, while DAMA may lead to increased risk of mortality and re-admissions. This study aims to identify frequency of patients who leave ED, determine their characteristics and identify associated factor. Methods: This was a retrospective observational study of patients that attended EDs of University Hospital Trust of Verona in 2017. Demographic and ED access associated variables were collected for LWBS, DAMA and completed-ED-treatment patients. Univariate and multivariate data analyses was based on EMUR-PS administrative data. Results: 5,901 of 127,180 ED accesses were uncompleted treatment (4.64%); LWBS were 4,664 (79.04%) and DAMA 1,237 (20.96%). Those who leave ED tended to be younger (39.35 vs. 45.56, p